Fatigue curve of microscale single-crystal copper: An in situ SEM tension-compression study. (1st April 2020) - Yan, Yabin; Sumigawa, Takashi; Wang, Xiaoyuan; Chen, Wufan; Xuan, Fuzhen; Kitamura, Takayuki
Highlights: Fatigue curve of micro-single-crystal Cu is obtained by in situ SEM fatigue tests. Cyclic hardening and softening appear in the early stage of fatigue. Large strain induces cyclic softening and secondary hardening in saturation stage. Small strain leads to only slight cyclic hardening in saturation stage. Fatigue life of micro-single-crystal Cu is much shorter than that of bulk. Abstract: A series of quantitative in situ tension-compression fatigue experiments in SEM are performed to investigate the fatigue curve of microscale single-crystal copper specimens with a test part of 1 × 1 × 2 μm under various strain amplitudes. The variation of resolved shear stress on the primary slip plane ( τ B4 ) and the corresponding evolution of crystallographic slips in each cycle are analyzed and in situ observed, respectively. The variation of τ B4 during fatigue shows that, (i) the variation of τ B4 clearly includes the early stage, the saturation stage, and the final fracture of the specimen; (ii) apparent cyclic hardening and softening appear in the early stage of all specimens; (iii) τ B4 shows a strain-dependent variation in the saturation stage. Continuous cyclic softening and secondary cyclic hardening occur in specimens with relatively higher strain, while only slight cyclic hardening emerges in the specimen with the minimum strain. Based on in situ SEM observations, the variation trend of τ B4 is interpreted from the evolution of geometrical characteristics of slip traces. Finally, we obtain the fatigue curve of microscale single-crystal coppers. The fatigue life is apparently dependent on the strain amplitude, while insensitive to the frequency of cyclic loading. Moreover, the fatigue lives of microscale single-crystal Cu are much shorter than those of bulks, indicating a significant size effect. The difference in fatigue lives of microscale and bulk ones reduces from about 360 to only 7 times with the decrease of applied strain, revealing the strain-dependence of size effect of fatigue life for microscale single-crystal coppers. Graphical abstract: Image, graphical abstract